2020
DOI: 10.31254/jmr.2020.6507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lockdown due to COVID-19 on Psychological Health of Young Adults- A Survey Report

Abstract: Background- Uncertainties are prevailing duringunprecedented COVID-19 outbreak time affecting higher studies/careers of undergraduate and graduate students. Aims- To identify symptoms of psychological problems existing in young adults in general and also, the effect of forced quarantine due to COVID-19lockdowns on their psychological behaviour. Setting and Design- A cross-sectional study through an online survey using 17+extended English version of the Strength and Difficulties questionnaire (SDQ) to measure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Here, the majority of the female adolescents had emotional and behavioral (hyperactivity) symptoms. Studies conducted during COVID-19 pandemic shows emotional symptoms is higher in girls than boys [2,3,9] and another study conducted among children and adolescents in Bangladesh prior to COVID-19 pandemic found girls had more emotional disorder, and boys have more behavioral disorder, [10] which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, the majority of the female adolescents had emotional and behavioral (hyperactivity) symptoms. Studies conducted during COVID-19 pandemic shows emotional symptoms is higher in girls than boys [2,3,9] and another study conducted among children and adolescents in Bangladesh prior to COVID-19 pandemic found girls had more emotional disorder, and boys have more behavioral disorder, [10] which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…The COVID 19 has led to rapid, unexpected changes to the lives of millions of adolescents and many of them are suffering from emotional and behavioral problems during this pandemic due to significant changes to daily life [1]. Recent studies have shown that the prevalence of behavioral problems among school-aged children in China varied from 4.7% to 10.3% in home quarantine during the COVID 19 outbreak, [2] and in India, effect of lockdown due to COVID19 on psychological health of young adults estimated that 16.9% and 18.2% of respondents are suffering from emotional and behavioral problems [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the result (Table 2), it was discovered that COVID-19 pandemic impacted more on the mental health of subjects between 19-40 years old than those who were 41 years old and above. This may imply that the fear associated with the spread of the virus due to its highly contagious nature which made government to impose restrictions and shutdown economic and social activities were more pronounced among this population group [10,15]. Furthermore, these physical and social restrictions of movement of people enforced mainly in the urban centers might have impacted more negatively on this group who are more active than the group aged 41 years and above.…”
Section: Discussionmentioning
confidence: 98%
“…For instance in their report Huang and Zhao [7] posited that COVID-19 have adverse effects on the mental health of the population. Furthermore Sabharwal et al [10] argued that Anxiety, lack of peer contact, reduced opportunities for stress regulation, induced restrictions on the free movement of people and stress due to future uncertainties regarding the pandemic has posed a great challenge to the mental health of urban dwellers. The pattern of findings noticed in this study on the mental health impacts of COVID-19 on urban dwellers corroborates Sabharwal et al's findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation